Object manipulation using haptic feedback based six hand areas in virtual reality - Ha, Chulwoo; Nam, Sanghun; Kwon, Joungheum (Edelweiss Applied Science and Technology, 2024)
Human hands are capable of performing various tasks through precise finger movements. If realistic finger movements are implemented in a virtual reality (VR) environment with the addition of haptic feedback, more precise interaction with virtual objects would become possible, leading to enhanced user immersion. This study proposes an object manipulation technique in a VR environment that utilizes five fingers along with haptic feedback. In particular, the technique allows users to manipulate objects using not only the fingertips but also the palms and finger phalanges. During manipulation, force and vibrotactile feedback are provided to ensure that the hand and objects do not penetrate each other, while allowing users to intuitively perceive the stiffness of objects. The study involved three tasks—stacking cubes, matching shapes, and throwing balls—which were used for both quantitative and qualitative evaluation. Results showed that users found the physical interactions with objects to be realistic and reported high levels of immersion. Although wearable devices imposed some physical strain and slightly increased the difficulty of object manipulation, mental load, stress, and distractions were relatively minimal. While the impact of combining free finger movements with haptic feedback on task performance has yet to be fully confirmed, the positive effects on user perception of realism and immersion were evident. The findings of this study could contribute to the development of advanced technologies that improve task performance and reduce fatigue in virtual environments.